Effect of betaine on growth performance and carcass composition of Alentejano pig breed. - Freitas, A.B. (2012)
The aim of this work was to evaluate the effect of fattening diets supplemented with betaine on growth performances and carcass characteristics of Alentejano pigs. Sixteen Alentejano pigs sexually neutralized, with a initial body weight (BW) of 36.3 kg, allocated to open-air individual pens (3m2), were divided into two experimental groups: Group C (n=8) consuming a commercial diet with 150 g/kg crude protein and 13.0 MJ digestible energy; and group CB (n=8) consuming the same diet supplemented with betaine (1g/kg). The diets were restrictively offered at 85% estimated ad libitum consumption. All pigs had free access to fresh water. Diet refusals were measured daily and pigs were weighed weekly. At 100 kg BW, pigs were submitted to a 24 h fasting period and killed. Carcass weight, backfat thickness and Longissimus muscle area were determined. The left side half carcass was submitted to commercial cuts according to the Portuguese norm and their weights recorded. No significant differences between treatments were detected in feed intake (297.3 vs. 286.5 kg), average daily gain (472 vs. 480g) and feed:gain (4.66 vs. 4.51). Hot carcass weight (82.2 vs. 83.6 kg), backfat thickness (5.0 vs. 5.3 cm), Longissimus muscle area (21.9 vs. 21.2 cm2) and weights of commercial cuts of the half carcass were also not significantly affected by betaine supplementation.